2023
DOI: 10.1093/geront/gnad054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Family Caregiver-Delivered MultiSensory Cognitive Stimulation Intervention for Older People With Dementia During Coronavirus 2019: A Randomized Controlled Trial

Abstract: Background and Objectives Many community dementia services such as home-visiting services and center-based activities were suspended during the COVID-19 pandemic. This study investigated the efficacy of a caregiver-delivered cognitive stimulation therapy (CDCST) on people with dementia during the pandemic. Research Design and Methods This was a two-arm randomized controlled trial involving 241 patient-caregiver dyads assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The caregiver's irritation, anger, or impatience can lead to greater agitation in PwD/MCI [40]. One study also reported that caregiver-delivered cognitive stimulation therapy showed significant improvements in cognition, behavioral and psychiatric symptoms, and the quality of life of PwD [41]. Therefore, training caregivers, and combining pharmacological and behavioral and/or family interventions targeting NPS, may alleviate suffering for a PwD, but also mediate improved caregiver well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The caregiver's irritation, anger, or impatience can lead to greater agitation in PwD/MCI [40]. One study also reported that caregiver-delivered cognitive stimulation therapy showed significant improvements in cognition, behavioral and psychiatric symptoms, and the quality of life of PwD [41]. Therefore, training caregivers, and combining pharmacological and behavioral and/or family interventions targeting NPS, may alleviate suffering for a PwD, but also mediate improved caregiver well-being.…”
Section: Discussionmentioning
confidence: 99%